AB0114 Prevalence of Antibodies Against Carbamylated Proteins in a Cohort of Italian Rheumatoid Arthritis Patients. (9th June 2015) - Pecani, A.; Alessandri, C.; Pendolino, M.; Mancini, R.; Spinelli, F.R.; Colasanti, T.; Barbati, C.; Sabatinelli, D.; Vomero, M.; Mastrangelo, A.; Di Franco, M.; Conti, F.; et al.
Abstract : Background: Carbamylation is a protein post-translational modification that can induces the production of antibodies. These antibodies, known as antibodies against carbamylated proteins (anti-CarP), have been recently identified in the sera of Rheumatoid Arthritis (RA) patients (1-3). Objectives: To determine the prevalence of anti-CarP in a cohort of Italian RA patients. Methods: 178 consecutive RA patients were recruited from the Rheumatology Outpatient Clinic of Sapienza University of Rome. All patients were diagnosed according to the 2010 ACR/EULAR criteria. Sixty-eight normal healthy subjects (NHS), sex and age matched, served as controls. Anti-CarP were detected by a solid phase "home-made" ELISA using carbamylated foetal calf serum as antigen (3). Anti-cyclic citrullinated peptide antibodies (anti-CCP) were determined by using the ImmunoCAP instrument (ELiA CCP2 assay, Phadia, Milan, Italy), whereas immunonephelometry (Behering, Marburg, Germany) was performed for rheumatoid factor (RF), as routinely used in clinical practice. Results: Anti-CarP were detected in 46.51% of the patients, anti-CCP in 63.3% while RF in 55.23% of them. Only 1 (1.47%) of the NHS was positive for anti-CarP, while none of them resulted positive for anti-CCP or RF. In RA patients, anti-CarP test showed a sensitivity of 45.93% (95, CI:38.32% to 53.68%) and a specificity of 98.53% (95%, CI:92.08%>99.96%). Anti-CarP showed a higher prevalence in RA patients than in the NHS (p=0.0001). A significant correlation between anti-CarP and anti-CCP as well as anti-CarP and RF (p=0.0005 and p=0.00001 respectively) was found. Conclusions: Our data confirm the presence of anti-CarP in the sera of RA patients. Their prevalence is significantly higher when compared to NHS. In this contest anti-CarP are highly specific for RA and correlate with anti-CCP and RF. References: Stoop JN et al., PloS One 2014. Jang X et al., Ann Rheum Dis 2014. Shi J et al., Ann Rheum Dis 2014. Disclosure of Interest: None declared